Challenges and opportunities for more integrated regional food security policy in the Caribbean Community. Issue 1 (1st January 2016) - Lowitt, Kristen; Saint Ville, Arlette; Keddy, Caroline S. M.; Phillip, Leroy E.; Hickey, Gordon M.
Abstract: The Caribbean Community (CARICOM) has recognized regional integration as an important development strategy for addressing the unique vulnerabilities of its member small island developing states (SIDS). Food security in the Caribbean is a fundamental social and ecological challenge in which the dynamics of regional integration are increasingly playing out. CARICOM members have subsequently identified a number of shared food security problems and have endorsed regional goals and approaches to address them; however, progress towards solutions has been slow. Recognizing that evidence-based studies on the potential factors limiting sustained progress are lacking, we undertook a comparative policy analysis to understand better the various approaches and framings of food security at national and regional levels with a view to assessing coherence. We identify considerable divergence in how regional and local policy institutions frame and approach food security problems in CARICOM and then identify ways through which the policy integration objectives for enhanced regional food security might be progressed, with a particular focus on social learning.